Connecting the dots between cell surface- and intracellular-triggered immune pathways in plants. (October 2022) - Bernoux, Maud; Zetzsche, Holger; Stuttmann, Johannes
Abstract: Plants can detect microbial molecules via surface-localized pattern-recognition receptors (PRRs) and intracellular immune receptors from the nucleotide-binding, leucine-rich repeat receptor (NLR) family. The corresponding pattern-triggered (PTI) and effector-triggered (ETI) immunity were long considered separate pathways, although they converge on largely similar cellular responses, such as calcium influx and overlapping gene reprogramming. A number of studies recently uncovered genetic and molecular interconnections between PTI and ETI, highlighting the complexity of the plant immune network. Notably, PRR- and NLR-mediated immune responses require and potentiate each other to reach an optimal immune output. How PTI and ETI connect to confer robust immunity in different plant species, including crops will be an exciting future research area. Highlights: NLRs oligomerize upon activation to function as ion channels or enzymes. PRRs and NLRs converge on common immune responses, including direct Ca 2+ influx. PRR and NLR immunity share genetic requirements and potentiate each other. Immune receptor networks and connections evolve differently in plant species.